2020
DOI: 10.3390/ijms21093281
|View full text |Cite
|
Sign up to set email alerts
|

Acid and Neutral Sphingomyelinase Behavior in Radiation-Induced Liver Pyroptosis and in the Protective/Preventive Role of rMnSOD

Abstract: Sphingomyelins (SMs) are a class of relevant bioactive molecules that act as key modulators of different cellular processes, such as growth arrest, exosome formation, and the inflammatory response influenced by many environmental conditions, leading to pyroptosis, a form of programmed cell death due to Caspase-1 involvement. To study liver pyroptosis and hepatic SM metabolism via both lysosomal acid SMase (aSMase) and endoplasmic reticulum/nucleus neutral SMase (nSMase) during the exposure of mice to radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…There are five different types of SMases [35], and these have been classified according to their ion dependence, location and optimal pH. These include lysosomal and plasma membrane acid SMase (aSMase) [36], endoplasmic reticulum/nucleus and plasma membrane neutral Mg 2+ -dependent and neutral Mg 2+ -independent SMase (nSMase) [37], alkaline SMase (alkSMase), which is present in the intestinal tract and human bile [35,38], and a Zn 2+ -dependent secreted form of aSMase [39]. Meanwhile, aSMase and nSMase are implicated in cellular signaling, whereas alkSMase is implicated in the degradation of SM incorporated in the diet.…”
Section: The Sphingomyelinase (Smase) Pathwaymentioning
confidence: 99%
“…There are five different types of SMases [35], and these have been classified according to their ion dependence, location and optimal pH. These include lysosomal and plasma membrane acid SMase (aSMase) [36], endoplasmic reticulum/nucleus and plasma membrane neutral Mg 2+ -dependent and neutral Mg 2+ -independent SMase (nSMase) [37], alkaline SMase (alkSMase), which is present in the intestinal tract and human bile [35,38], and a Zn 2+ -dependent secreted form of aSMase [39]. Meanwhile, aSMase and nSMase are implicated in cellular signaling, whereas alkSMase is implicated in the degradation of SM incorporated in the diet.…”
Section: The Sphingomyelinase (Smase) Pathwaymentioning
confidence: 99%
“…The nSMase family includes four isoforms, nSMase1, nSMase2, nSMase3, and nSMase4 encoded by four different genes SMPD2, SMPD3, SMPD4, and SMPD5, respectively [25]. nSMase1 is located in the reticulum endoplasmic/Golgi apparatus and in the cell nucleus and it was involved in apoptosis and cancer; nSMase2 is specific of the plasma membrane and it was involved in exosome formation, and in the inflammatory response; nSMase3 is located in endoplasmic reticulum and it was involved in cellular stress response; nSMase4 belongs to the mitochondria and its function is not yet clear in human cells [25]. In cancer: (a) aSMase was able to reprogram the tumor immune microenvironment [26] and to participate in apoptotic cell death [27,28]; (b) nSMase1 had both proand anti-cancer roles [29].…”
Section: Introductionmentioning
confidence: 99%
“…These effects are attenuated by the administration of recombinant manganese superoxide dismutase (rMnSOD). Importantly, rMnSOD counteracts the radiation-induced liver damage exerting a protective role via acid sphingomyelinase (aSMase), and a preventive role via neutral sphingomyelinase (nSMase) [16]. Cataldi et al also demonstrated that nSMase is responsible for the preventive and protective effect elicited by rMnSOD against radiation-induced damage in the brain [17].…”
mentioning
confidence: 99%